COLOUR-BLIND GLOBALIZATION AND DEVELOPMENT - Kumar, Ajit (European Scientific Journal, ESJ, 2015)
Globalization as a narrative seldom extends well beyond the vicissitudes of interpretations. But be it Hyperglobalists, Sceptics or Transformationalists, for all of them, it is understood and practiced in terms of ‘Global Connectivity’ and ‘Global Community’. Many a time, this global connectivity and community is assumed to be given and inevitable. But reality belies the truth as globalization comes to many with so many filters. Many of the agents of globalization are colour blind, of course not literally but in generic sense. They pose themselves as custodians of globalization and development and thus decide up to a greater extent who becomes the part of the global connectivity and global community. What is mindboggling in all this customized version of globalization is the fact that this stake-out is based on the colour of the body! One can easily guess by now that this particular colour would be most probably ‘black’ or some variant of it and also can smack of racism instantly. There are many people in the southern part of India who share the black colour of their bodies. At the same time there is a sizable population of people who share the fair complexion of their bodies. Based on a primary survey this paper explains the modus operandi through which the people sharing black colour of their bodies have been kept out of bounds in regard to globalization and its fruits and also depicts the saga of struggles of these black people and the niche they have carved out in society for themselves with the help of Christians.